1996
DOI: 10.1016/s0969-2126(96)00073-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a new heat-labile enterotoxin, LT-IIb

Abstract: The structure of LT-IIb provides insight into the sequence diversity and structural similarity of the AB5 toxin family. New knowledge has been gained regarding the assembly of AB5 toxins and their active-site architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 65 publications
3
91
0
Order By: Relevance
“…LT-IIb-B 5 and other B pentamers of heat-labile enterotoxins can participate in both hydrophilic and hydrophobic interactions (42,43). The so-called "lower end" of the B pentamer pore of LT-IIb interacts through hydrophilic interactions with the extracytoplasmic oligosaccharide moiety of GD1a, which is anchored to the cell membrane via an intramembrane ceramide lipid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LT-IIb-B 5 and other B pentamers of heat-labile enterotoxins can participate in both hydrophilic and hydrophobic interactions (42,43). The so-called "lower end" of the B pentamer pore of LT-IIb interacts through hydrophilic interactions with the extracytoplasmic oligosaccharide moiety of GD1a, which is anchored to the cell membrane via an intramembrane ceramide lipid.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called "lower end" of the B pentamer pore of LT-IIb interacts through hydrophilic interactions with the extracytoplasmic oligosaccharide moiety of GD1a, which is anchored to the cell membrane via an intramembrane ceramide lipid. The "upper end" of the B pentamer pore contains a large hydrophobic surface (549 Å 2 ) that engages in hydrophobic interactions with the A2 subcomponent of the A subunit; however, this hydrophobic surface area is solvent-accessible in the absence of the A subunit (42,43). Because of the absence of an A subunit, LT-IIb-B 5 might, therefore, be free to interact with TLR2 or other receptors that depend on hydrophobic interactions for ligand binding (44 -46).…”
Section: Discussionmentioning
confidence: 99%
“…Both the structures and functions of the type II HLT are related to the structures and functions of type I HLT (27,54). Type I and type II HLT are oligomeric proteins composed of an A polypeptide which is noncovalently coupled to a pentameric array of B polypeptides.…”
mentioning
confidence: 99%
“…6A); this result is unlikely to reflect residual catalytic activity because LT-IIb-B 5 behaved similarly to LT-IIb(S59K/ E110K). In this regard, we have shown that low-level cAMP induction by LT-IIb-B 5 probably involves TLR2-dependent production of PGE 2 (Fig. 6B, inset) because inhibition of PGE 2 synthesis by indomethacin also inhibited cAMP induction by LT-IIb-B 5 (Fig.…”
Section: Construction Of Mutagenically Detoxified Mutants Of Lt-iibmentioning
confidence: 82%
“…1). The actual catalytic moiety is the A1 subcomponent, which is formed by proteolytic cleavage and reduction of an intrachain disulfide bond in the A polypeptide, while the A2 subcomponent at the C-terminal end of the A polypeptide is inserted noncovalently into the central pore of the ring-shaped B pentamer (2,3). The B pentamer in itself is nontoxic but binds with high affinity to gangliosides, a heterogeneous family of glycolipids found on most cells (4), and delivers the A subunit into the cells (1).…”
mentioning
confidence: 99%